A especialização do mandado de segurança coletivo na tutela dos direitos coletivos no Brasil - Paula Iochino Valerio (2012)
This is the research developed in the course of the Masters Degree Program of Law of the Federal University of Minas Gerais. Advancing in the study of Collective Procedural Law, it aims to demonstrate that the peculiarities of the object and procedure of collective writ of mandamus must exist and make preferential use of this specific instrument of protection, although there are other generic procedural possibilities and techniques able to protect, at least in theory, the same rights protected through it. It has as theoretical boundary reaffirming the instrumentality of procedure, more specifically the idea of specialization of the jurisdiction, the theory presented by Humberto Theodoro Jr. and also developed by Jose Roberto dos Santos Bedaque, supporting that the need for judicial protection is differentiated, in order to provide the citizen of results which are compatible with the requirements of substantive law. The research is interdisciplinary, with research in the areas of Constitutional Law, Procedural Law, Collective Procedural Law and Comparative Law, from the legal-dogmatic and legal-sociological aspects.